Identifying stakeholder preferences for communicating impact from medical research: a mixed methods study - Katherine Pitrolino; Buddhini Samarasinghe; Andy Pringle; Ian Viney (BMC, 2024)
Abstract Background Documentation of research outcomes using impact case studies (ICS) is increasingly required to demonstrate the wider societal benefits of research. However, there is limited evidence of the best way to communicate research outcomes using ICS, especially when highlighting research impact that is not part of a research assessment programme. This study aims, for the first time, to analyse expectations, and methods of communicating impact from medical research across a varied set of stakeholders relevant to the Medical Research Council (MRC). Methods Impact narratives about outcomes and impact from MRC research were evaluated using an online survey and in depth semi-structured interviews. Participants were recruited from internal MRC databases and included early career and senior management academics as well as representatives from industry, healthcare, charities, and the government. Informed consent was gained prior to data collection and the study was approved by the university's research ethics committee. Qualitative and quantitative analysis determined stakeholder preferences for ICS content, language and presentation as well as capturing themes and perspectives on the concept of research impact. Results 193 participants responded to the online survey exploring definitions of impact and methods of communicating medical research outcomes. The work uncovered expectations of improved health and wellbeing as well as knowledge generation via publications and citations. In depth interviews with sixteen participants demonstrated preferences for clear, easy to read content that focused on facts and evidence and avoided both academic and hyperbolic language. Emergent themes from this work revealed that ICS need to quickly capture imagination and grab attention, while the views and expectations are quite different to press releases and are audience specific. Conclusions The content of ICS often focuses on non-academic impacts; however this work highlighted that evidence of academic impacts were outcomes highly valued by stakeholders relevant to the MRC. This work examined a new typology of ICS attributes, which emphasised that the language and presentation of impact narratives can influence the perception of research outcomes, providing useful information for individuals and organisations using ICS to showcase their research. It also shows that if ICS attempt to communicate challenges and issues around achieving impact from research, they may be more credible and useful to their intended audience.